Bimbingan Teknis bagi Guru melalui Program Pencegahan Perundungan pada SMK Permata Kemiri Kabupaten Tangerang - Winanti Winanti; Istjib Kulla Himmy’azz; Dwi Ferdiyatmoko Cahya Kumoro; Karnawi Kamar; Erick Fernando; Nurasiah Nurasiah; Yayah Yulia; Adiyanto Adiyanto; Marhaendro Purno; Bayu Suseno; Yoga Prihastomo; Fajar P (IAHN Gde Pudja Mataram, 2023)
Bullying among adolescents, especially vocational school students, still often occurs, which starts from joking and insulting each other on purpose and in the end leads to bullying. Technical guidance is intended for teachers and school elements, carried out for one day with three speakers including a psychologist. The involvement of all elements of the school in this technical assistance aims to provide understanding and education to all elements of the school, especially teachers to understand the symptoms of bullying, types, behavior, impacts, and ways to prevent bullying. The technical guidance went smoothly and ended with a discussion and questions and answers as well as group photos. This technical guidance is expected to assist teachers and all elements of the school in early detection and dealing with bullying experienced by students.